Philippines : Report on the Observance of Standards and Codes (ROSC)-Data Module. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This data module of the Report on the Observance of Standards and Codes (ROSC) provides a summary assessment of dissemination practices in the Philippines relative to the Special Data Dissemination Standard (SDDS). It presents a summary assessment of data quality for national accounts, consumer price, producer price, balance of payments, government finance, and monetary statistics, based on the Data Quality Assessment Framework (DQAF). The assessment reveals that the statistical system of the Philippines is sustained by generally strong legal and institutional frameworks and solid methodological foundations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet